(untitled) (Modern education and development, 2025)
This article explores innovative and developmentally appropriate methods for teaching English in preschool institutions in Uzbekistan. As the demand for English proficiency grows in the country, introducing the language at an early age becomes increasingly important. This paper presents the pedagogical rationale for early English instruction, outlines effective teaching methods tailored for young learners, and discusses challenges and recommendations specific to the Uzbek preschool context. The findings suggest that with the right strategies—such as play-based learning, storytelling, and Total Physical Response—preschool children can successfully begin learning English in an enjoyable and productive manner.